2014
DOI: 10.1073/pnas.1402739111
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-finger protein ZFP318 is essential for expression of IgD, the alternatively splicedIghproduct made by mature B lymphocytes

Abstract: IgD and IgM are produced by alternative splicing of long primary RNA transcripts from the Ig heavy chain (Igh) locus and serve as the receptors for antigen on naïve mature B lymphocytes. IgM is made selectively in immature B cells, whereas IgD is coexpressed with IgM when the cells mature into follicular or marginal zone B cells, but the transacting factors responsible for this regulated change in splicing have remained elusive. Here, we use a genetic screen in mice to identify ZFP318, a nuclear protein with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 43 publications
5
77
0
Order By: Relevance
“…Indeed, B cells lacking Mef2c still express IgD (28) suggesting that sufficient Zfp318 was present to allow for Ighd transcription. The analyses of our Zfp318 deficiency via Vav-Cre phenocopies the results described by Enders, et al, although a relative depression of T2 B cells of the spleen was not noted in their report (15). Enders, et al, further suggested that Zfp318 served to regulate IgD production by controlling the alternative splicing of the hnRNA of the Ighm/Ighd locus although no data were presented to support this model (15).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Indeed, B cells lacking Mef2c still express IgD (28) suggesting that sufficient Zfp318 was present to allow for Ighd transcription. The analyses of our Zfp318 deficiency via Vav-Cre phenocopies the results described by Enders, et al, although a relative depression of T2 B cells of the spleen was not noted in their report (15). Enders, et al, further suggested that Zfp318 served to regulate IgD production by controlling the alternative splicing of the hnRNA of the Ighm/Ighd locus although no data were presented to support this model (15).…”
Section: Discussionsupporting
confidence: 86%
“…The analyses of our Zfp318 deficiency via Vav-Cre phenocopies the results described by Enders, et al, although a relative depression of T2 B cells of the spleen was not noted in their report (15). Enders, et al, further suggested that Zfp318 served to regulate IgD production by controlling the alternative splicing of the hnRNA of the Ighm/Ighd locus although no data were presented to support this model (15). Our conclusions as to the proposed function of Zfp318 differ from those presented of Enders, et al due to our RNA-Seq data which point to the regulation of transcription termination as the event which subsequently allows for the production of IgD via alternative splicing.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…2f,g). To exclude differences in transgene integration site between the MD4 and MM4 animals, we also prevented IgD co-expression in MD4:ML5 transgenic mice by breeding with a Zfp318 null allele22. Accumulation of anergic mature B cells was diminished in Zfp318 −/− MD4:ML5 transgenic mice where the B cells only expressed IgM HEL (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immature B cells begin by expressing only IgM, but IgD co-expression progressively increases as they become transitional and mature B cells in the spleen due to increased expression of Zfp318 (ref. 22), which facilitates alternative mRNA splicing of the heavy chain variable (VDJ H ) exon to either IgM or IgD heavy chain constant (C)-region exons. This arrangement is evolutionarily preserved in most species of fish, amphibians, reptiles, birds and mammals1723, yet mice lacking IgD have normal B cell development and only slightly delayed antibody responses2425.…”
mentioning
confidence: 99%